Hubungan status gizi dengan kebugaran jasmani siswa SMP - Ferani, Kadek Dila Selvia; Kurniasari, Septi; Oktavia, Santi (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Physical fitness is the body's ability and capability to make adjustments and adaptations to the physical release given to it from daily work without causing excessive fatigue. Physical fitness is a need that must be met so that we can carry out daily life activities well. Nutrition is an important part of the health sector and receives serious attention from the government. Good nutrition is the foundation for public health. The influence of nutritional problems on growth, development, intellectual, and productivity shows the great role of nutrition in human life. Purpose: To find out whether there is a relationship between nutritional status and physical fitness of junior high school students. Methods: Quantitative research with cross-sectional design conducted at SMP Perjuangan, Sekampung Udik District, East Lampung Regency. Data were collected using questionnaires, tests, and in-depth interviews. The sampling technique used was accidental sampling and obtained 50 people as respondents in the study. Data analysis used the Chi-Square Test statistical test with a degree of confidence p <0.05. Results: The chi square test shows a p-value=0.000 (<0.05) which indicates that there is a significant relationship between BMI and physical fitness. This means that the more ideal the nutritional status (normal BMI), the higher the child's physical fitness. Conclusion: There is a relationship between nutritional status and physical fitness of junior high school students. Keywords: BMI; Nutrition; Physical Fitness. Pendahuluan: Kebugaran jasmani adalah kesanggupan dan kemampuan tubuh melakukan penyesuaian adaptasi terhadap pembebasan fisik yang diberikan kepadanya dari kerja yang dilakukan sehari-hari tanpa menimbulkan kelelahan yang berlebihan. Kebugaran jasmani merupakan suatu kebutuhan yang harus dipenuhi agar kita dapat menjalankan aktivitas kehidupan sehari-hari dengan baik. Gizi merupakan bagian dari sektor kesehatan yang penting dan mendapat perhatian serius dari pemerintah. Gizi yang baik merupakan fondasi bagi kesehatan masyarakat. Pengaruh masalah gizi terhadap pertumbuhan, perkembangan, intelektual, dan produktivitas menunjukkan besarnya peranan gizi bagi kehidupan manusia. Tujuan: Untuk mengetahui apakah ada hubungan status gizi dengan kebugaran jasmani siswa SMP. Metode: Penelitian kuantitatif dengan desain cross-sectional yang dilakukan di SMP Perjuangan Kecamatan Sekampung Udik Kabupaten Lampung Timur. Data dikumpulkan dengan menggunakan kuesioner, tes, dan wawancara mendalam. Teknik pengambilan sampel yang digunakan accidental sampling dan diperoleh sebanyak 50 orang menjadi responden dalam penelitian. Analisis data menggunakan uji statistik Chi-Square Test dengan derajat kepercayaan p<0.05. Hasil: Uji chi square menunjukkan p-value = 0.000 (<0.05) yang menunjukkan bahwa terdapat hubungan yang signifikan antara IMT dengan kebugaran jasmani. Artinya semakin ideal status gizi (IMT normal), maka semakin tinggi kebugaran jasmani anak. Simpulan: Ada hubungan status gizi dengan kebugaran jasmani siswa SMP. Kata Kunci: Gizi; IMT; Kebugaran Jasmani.